Discontinuity of overhanging melt track in selective laser melting process. (December 2020) - Le, K.Q.; Wong, C.H.; Chua, K.H.G.; Tang, C.; Du, H.
Highlights: Discontinuities were found in both simulation and experiment of the overhang. Applying high laser power at high energy density can alleviate the discontinuities. Using high laser power at low energy density can eliminate pores, and warpage. ABSTRACT: This study shares a side-by-side numerical and experimental examination on the features of overhanging structure in the SLM process. The simulation model was achieved by incorporating Fresnel reflections in the laser beam through the ray-tracing model. The CFD model was employed to investigate different overhanging situations, including perpendicular and parallel overhanging melt tracks on a cuboid block, as well as parallel melt tracks on an inclined block. The process parameters are found to strongly affect the surface morphologies of the overhanging melt track where voids caused by interfacial instability and geometrical defects namely discontinuities were observed. The subsequent defects caused by the discontinuity have also been investigated in both simulation and experiment. In the range of this study, it found that high laser power alleviates the discontinuity phenomenon of the overhanging melt track. However, by applying high laser power at high energy density, the high value of melt pool depth was formed, causing warpage to the overhanging printed part. Nevertheless, employing high laser power while maintaining low energy density can eliminate phenomenon such as irregular pores, partially-melted powder, deep melt pool formation and geometrical inaccuracy. Graphical Abstract: Graphical Abstract Image, graphical abstract